Is Welfare Working? A qualitative longitudinal multi-case study on the experiences of young unemployed people engaging with Active Labour Market Policies, in the North-East of England - RICH, STEPHANIE,FRANCES (2018)
This thesis explores the lived experiences of 28 young people in seven locations in the North-East of England who were unemployed and engaging with aspects of Active Labour Market Policies (ALMPs) between 2012 and 2014. The research set out to give young people who were directly affected by these Active Labour Market Policies, particularly in the context of shifting levels of support for young unemployed people and increasing conditionality and sanctions associated to benefits, a voice about how this was impacting on them. The research adopted a qualitative longitudinal multi-case study approach. The findings document the young people’s barriers to employment and their related perspectives and experiences of the JobCentre Plus in particular as an interface of the government’s ALMPs. It was found that corrective methods to unemployment kept churning these young people between being off benefits, albeit short-term, and back on again as new claimants. It was not a simple case of young people choosing not to work; there was an inter-play between structure and agency. The structure of place and institutions that interacted with these young people shaped the choices the young people chose or were able to make. Here the research argues that the structure of agency needs to be addressed in order to tackle youth unemployment